Improving Rumi Reading Proficiency thorugh Literature Circle Model at Phitakvitayak Kumung School Southern Thailand - Inda Sari; Nikmah Sari Hasibuan; Khatib Lubis; Sumaiyah Menjamin; ⁠Nor Mita Ika Saputri (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study investigates the impact of the Literature Circle model on enhancing Malay Rumi reading proficiency and critical thinking skills among Mattayom 1 students at Phitakvitayak Kumung School in Southern Thailand. Adopting a quantitative experimental design, the research utilized pre-test and post-test assessments to evaluate changes in students’ reading performance, analyzed using SPSS. The results indicate a statistically significant improvement in reading proficiency following the intervention. For example, one student’s score increased from 60 to 80, reflecting a 20-point gain; similar improvements were recorded across the cohort. A paired sample t-test confirmed the significance of these gains, yielding a t-value of 58.169 and a p-value of 0.0001 (p < 0.05). Additionally, participation in Literature Circle discussions fostered the development of critical thinking abilities, including text analysis, questioning techniques, and comparative reasoning. This study contributes to the expanding field of collaborative literacy instruction by providing empirical evidence for the effectiveness of the Literature Circle model in multilingual, cross-cultural, and minority language contexts. Specifically, it advances the understanding of Rumi Malay pedagogy an area that remains under-explored by highlighting the model's potential to enhance both reading proficiency and higher-order thinking skills among learners in Southern Thailand.